PERAN PERILAKU KEWARGANEGARAAN ORGANISASI-INDIVIDU (OCB-I) PADA KINERJA KARYAWAN DAN NIAT UNTUK KELUAR DENGAN KETERIKATAKAN KARYAWAN SEBAGAI VARIABEL MEDIASI (STUDI KASUS DI ESTHY CAKE & BAKERY YOGYAKARTA) - Danang Sunyoto; Yanuar Saksono; Nurwiyanta Nurwiyanta; Krismonika Lubis (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to examine the role of OCB-I on performance and intention to leave with employee engagement as mediation. Methodology/Samples/Approach–Method of data collection by questionnaire. Methods of data analysis using regression analysis with SPSS computer program. The population research model is 59 employees. Quantitative analysis approach. Research Results–Individuals' direct organizational citizenship behavior plays a positive role on employee engagement, performance, and intention to leave. Besides that, employee engagement plays a positive role on performance and intention to leave. However employee engagement is not a direct mediator of individual organizational citizenship behavior on performance and intention to leave.